Problems of Elementary School Business Education: Systematic Literature Review (SLR) - Bakhrudin Bakhrudin; Najimul Baldan; Amar Ma'ruf Genteng; Aniek Indrawati; Ludi Wishnu Wardana (Pusat Riset dan Inovasi Nasional, 2023)
Formal education, especially in basic education in entrepreneurship learning, has a big challenge to be able to provide enlightenment to students through the learning process about the need for entrepreneurial behavior that is not only self-oriented, but economic behavior that must also be oriented to the interests of the people, through entrepreneurship learning. Research objectives 1) application of business education 2) economic learning curriculum 3) entrepreneurial behavior of elementary school formal education students. The method used in this research is Systematic Literature Review (SLR) by collecting and analyzing journals related to keywords. Based on the literature study conducted, it was found that entrepreneurship learning does not stand alone in the 2013 curriculum, but merges into other subjects such as Cultural Arts and Crafts to introduce students to currency, production and buying and selling processes, while populist economics learning blends into the subject PPKn lessons understand the Pancasila precepts as the basic foundation of populist economic education.